2006
DOI: 10.3327/jnst.43.159
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Microstructure and Microchemistry in Cold-worked 316 Stainless Steels under PWR Irradiation

Abstract: The evolution of microstructures and microchemistry was examined by transmission electron microscopy in coldworked SUS 316 stainless steel components irradiated in a pressurized water reactor to 1-73 dpa at 565-596 K. Homogenous nucleation of dislocation loops, helium bubbles and 0 precipitates was detected. The dislocation loops consisted of a high density of Frank loops and black dots. The black dots are considered to be small Frank loops, some fraction of which could be vacancy-type. The size distribution s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 20 publications
3
20
0
Order By: Relevance
“…The irradiation temperature and dose rate were 293°C, 6 Â 10 À9 dpa/s for 2 dpa, 323°C, 2.8 Â 10 À8 dpa/s for 11 dpa, 323°C, 5.4 Â 10 À8 dpa/s for 22 dpa, 298°C, 7.8 Â 10 À8 dpa/s for 38 dpa and 305°C, 1.5 Â 10 À7 dpa/s for 73 dpa. Microstructure, grain boundary segregation and hardness were already examined in the previous study [16]. The data in the previous study indicated that evolution of microstructure, segregation and hardness mainly depended on dose although both dose rate and temperature were expected to affect the evolution to some extent.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…The irradiation temperature and dose rate were 293°C, 6 Â 10 À9 dpa/s for 2 dpa, 323°C, 2.8 Â 10 À8 dpa/s for 11 dpa, 323°C, 5.4 Â 10 À8 dpa/s for 22 dpa, 298°C, 7.8 Â 10 À8 dpa/s for 38 dpa and 305°C, 1.5 Â 10 À7 dpa/s for 73 dpa. Microstructure, grain boundary segregation and hardness were already examined in the previous study [16]. The data in the previous study indicated that evolution of microstructure, segregation and hardness mainly depended on dose although both dose rate and temperature were expected to affect the evolution to some extent.…”
Section: Methodsmentioning
confidence: 96%
“…Typical grain size was about 20-30 lm. The details of the tube material were described elsewhere [16]. In this study, experiments were conducted on specimens cut from several positions of the tubes, where the neutron doses were 2, 11, 22, 38 and 73 dpa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the low-dose-rate region of 10 À8 to 10 À6 dpa/s relevant to reactor irradiation, LWR data were reported at temperatures of 560-623 K at a dose rate of 10 À8 -10 À7 dpa/s. 8,11,12,40,41) At doses of 10-20 dpa, Cr depletion and Ni enrichment were 4-7 wt% and 10-14 wt%, respectively. Fast breeder reactor (FBR) data were also reported at a temperature of 593-653 K at a dose rate of 10 À7 -10 À6 dpa/s.…”
Section: Resultsmentioning
confidence: 99%
“…In commercial stainless steels, Mo is often enriched up to 10 wt% in unirradiated steels at grain boundaries and that Si reaches several wt% in stainless steels irradiated to several dpa, corresponding to a level higher than 10 at%. 8,11,12) Such high concentration of Mo and/or Si is likely to strongly affect RIS of major elements.…”
Section: Introductionmentioning
confidence: 99%